Efficacy of NiTi rotary instruments in removing calcium hydroxide dressing residues from root canal walls - Kuga, Milton Carlos [UNESP]; Campos, Edson Alves de [UNESP]; Faria-Junior, Norberto Batista de [UNESP]; Só, Marcus Vinicius Reis; Shinohara, André Luis (Sociedade Brasileira de Pesquisa Odontológica (SBPqO), 2012)
The aim of this study was to evaluate the efficacy of three rotary instrument systems (K3, ProTaper and Twisted File) in removing calcium hydroxide residues from root canal walls. Thirty-four human mandibular incisors were instrumented with the ProTaper System up to the F2 instrument, irrigated with 2.5% NaOCl followed by 17% EDTA, and filled with a calcium hydroxide intracanal dressing. After 7 days, the calcium hydroxide dressing was removed using the following rotary instruments: G1 - NiTi size 25, 0.06 taper, of the K3 System; G2 - NiTi F2, of the ProTaper System; or G3 - NiTi size 25, 0.06 taper, of the Twisted File System. The teeth were longitudinally grooved on the buccal and lingual root surfaces, split along their long axis, and their apical and cervical canal thirds were evaluated by SEM (×1000). The images were scored and the data were statistically analyzed using the Kruskall Wallis test. None of the instruments removed the calcium hydroxide dressing completely, either in the apical or cervical thirds, and no significant differences were observed among the rotary instruments tested (p > 0.05).
Keywords: Endodontics; Calcium Hydroxide; Dentin